The influence of situational inhibitors on engagement in informal workplace learning activities amongst Malaysian accountants: A conceptual framework - Abdul Wahab, Muhammad Syahir; Saad, Ram Al Jaffri; Mat Samsudin, Mohd Amir (2015)
This paper aims to propose a conceptual framework for examining the influence of situational inhibitors on engagement in informal learning activities amongst Malaysian accountants.An extensive literature review method was utilized to identify and analyse relevant literatures in order to propose the conceptual framework.This paper identified four situational inhibitors of engagement in informal learning activities.The inhibitors are lack of time due to heavy workload, lack of proximity to colleagues’ working areas, lack of support from others and structural inhibitor.Theoretical and practical implications of the paper as well as suggestions for future research were also discussed.